2001
DOI: 10.1037/0022-0167.48.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Career development in adolescence as a family project.

Abstract: This study conceptualizes and investigates career-relevant parent-child conversations and other actions over time as a family project. Dyads composed of a parent and an adolescent from 20 families participated in a videotaped career-related conversation to determine a family career-development project that was subsequently monitored for a 6-month period and followed up with a 2nd videotaped conversation. On the basis of a systematic qualitative analysis, several dimensions were identified as facilitating the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 45 publications
5
112
0
6
Order By: Relevance
“…When parents try to enforce their own ideas on their offspring's career development, these practices are likely to inhibit youths' sense of autonomy and erode their intrinsic motivation (Deci & Ryan, 1985;Ryan & Deci, 2000). Accordingly, previous research has found that youths under over-controlling parental practices are more passive in their career preparation, and displayed a high level of behavioral inhibition and lack of exploration activities (Grotevant & Cooper, 1988;Young et al, 2001). Therefore, in current research we also propose that parental career interference will be negatively related to career exploration, and will also has a negative effect on career adaptability.…”
Section: The Roles Of Parental Career-specific Behaviorsmentioning
confidence: 99%
“…When parents try to enforce their own ideas on their offspring's career development, these practices are likely to inhibit youths' sense of autonomy and erode their intrinsic motivation (Deci & Ryan, 1985;Ryan & Deci, 2000). Accordingly, previous research has found that youths under over-controlling parental practices are more passive in their career preparation, and displayed a high level of behavioral inhibition and lack of exploration activities (Grotevant & Cooper, 1988;Young et al, 2001). Therefore, in current research we also propose that parental career interference will be negatively related to career exploration, and will also has a negative effect on career adaptability.…”
Section: The Roles Of Parental Career-specific Behaviorsmentioning
confidence: 99%
“…Callings can therefore be seen as either having a religious or a 'secular, inner-directed' quality (Hall & Chandler, 2005 (Blustein, 2011;Bryant Zvonkovic, & Reynolds, 2006;Young et al, 2001). India exhibits midlevel collectivism with high power distance between members, where the duty towards others and 'serving and sacrificing' for the in-group is seen as the norm (Singelis, Triandis, Bhawuk, & Gelfand, 1995, p. 244).…”
Section: Literature Overview Callingsmentioning
confidence: 99%
“…Family communication is central to generativity (Young et al, 2001), where the recipients of generative communication are found to imbibe the values inherent in transmitted messages. For example, a longitudinal study by Pratt, Norris, Hebblethwaite, and Arnold (2008) found that a greater number of life interventions by more generative parents were associated with greater adolescent acceptance of conveyed value messages.…”
Section: Literature Overview Callingsmentioning
confidence: 99%
“…Additionally, research has acknowledged the impact of external factors, for example the environment in which an individual was raised and her or his socialisation experiences, family expectations and needs, life circumstances, spiritual and religious factors, and social service motivation upon the internal expectations and beliefs regarding her or his career trajectory Fouad, 2007;Greenhaus and Powell, 2006;Halpern, 2005;Schultheiss, 2006). For example, family expectations and needs can restrain the individual's career choices (Greenhaus et al, 2001;Halpern, 2005), but family can also contribute to extending and enhancing the options available to a given person, through providing her or him with financial and emotional support, networking and social resources (Pearson and Bieschke, 2001;Schultheiss, 2003;Young et al, 2001). Similarly, life circumstances can have both negative -as in the case of poverty, marginalisation, or stigmatisation (Arnold and Doctoroff, 2003;Blustein et al, 2002) -and positive impacts, for example through presenting individuals with random, serendipitous occurrences, leading to beneficial career outcomes for them (Mitchell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%